Incidencia De La Gestión Pública En La Mejora De Los Servicios De Atención De La Empresa Quevial Ep, Cantón Quevedo, Año 2023. - Carpio Vanegas , Blanca Priscila (2025)
The problem addressed in this study focused on the question: How does public management influence the quality of the services provided by QUEVIAL EP in the canton of Quevedo in 2023? The main objective was to determine how public management impacts the quality of QUEVIAL EP’s services in the canton of Quevedo during the year 2023. The methodology was based on field, exploratory, descriptive, and qualitative- quantitative research approaches. The methods applied included inductive, deductive, and analytical methods. The population consisted of 31 employees from QUEVIAL EP, with the sample encompassing the entire population: one maintenance department head and employees from the same department, divided into 22 from the mechanical area and 8 from the electrical area. The techniques used included observation, interviews, and surveys, with the instruments being an observation form and a structured questionnaire, respectively. The most relevant results revealed a critical perception of the quality of services, directly influenced by public management. Deficiencies in resources, training, communication, and autonomy were identified as the main factors affecting the performance of the maintenance department. The most significant conclusions highlight that public management has a substantial impact on the quality of QUEVIAL EP’s services. Through administrative processes, resource allocation, and policy implementation, it was evident that efficient public management improves service quality. Additionally, areas for improvement were identified in operational management and staff training, which must be reinforced to ensure the sustainability of improvements over the long term.